ANALISIS KESALAHAN PENGGUNAAN EJAAN DALAM MENULIS TEKS NARASI PADA SISWA KELAS IV SEKOLAH DASAR - Eki Elviawati; Eko Kuntarto; Eka Sastrawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Error analysis in this study is to investigate what spelling mistakes are made by students in writing a narrative text. The purpose of this research is to find out (1) the types of spelling errors in punctuation in writing narrative texts of grade IV elementary school students, (2) the types of spelling errors in capital letters in writing narrative texts of grade IV elementary school students, (3) the types of spelling errors in writing narrative texts in writing words of grade IV elementary school students, and (4) the level of spelling errors in writing narrative texts of grade IV elementary school students. This research was conducted at SDN 13/I Rengas Condong. This research involved IVA grade students of SDN 13/I Rengas Condong which amounted to 17 students. this research used a qualitative approach with the category analysis method. Data collection techniques were taken from performance tests and observation. The results of the study show that regarding the analysis of students' errors in using Indonesian spelling when writing a narrative text, the forms of these errors were found, including (1) errors in the use of capital letters totalling 348 errors with a percentage of 48.20%, which in the capital letter errors are still grouped into smaller groups. (2) word writing errors totalling 124 errors with a percentage of 17.17%, where the errors are still grouped into smaller groups, (3) punctuation errors totalling 250 errors with a total percentage of 34.62%, where the punctuation errors are still grouped into smaller groups. At the level of spelling errors, the category of errors mostly made by students lies in the very low category with the type of punctuation writing errors whose presentation is below 10%, and there are 3 students who fall into the low category where it occurs in the type of capital letter writing errors and word writing errors with a percentage above 11%.